Keragaman Familia Tumbuhan Obat Masyarakat Kota Parepare Sulawesi Selatan - Alfiyah Mutmainnah; Elis Tambaru; Andi Masniawati Zainuddin (Fakultas MIPA UNM, 2020)
Abstract. The research is Diversity of Medicinal Plants Families in the Community of Parepare City, South Sulawesi was conducted in Parepare city on September-October 2020. The ethnobotany research of the Parepare’s people to uncover the local knowledge of the community in utilizing the diversity of plants as medicinal plants. The method used in this research is interview, observation and documentation. Data was collected in four subdistricts in Parepare City, namely Ujung subdistrict, Soreang subdistrict, Bacukiki subdistrict and West Bacukiki subdistrict. The number of informants in this study were 100 people. Ethnobotany data collected in the form of community knowledge about natural resources of plants used as traditional medicinal ingredients. The Parepare’s people use 86 species of plants consisted of 40 families as medicinal materials. Zingiberaceae is the most widely uses species. Parepare’s people used 10 species medicinal plants from Zingiberaceae.Keywords: Diversity, Familia, medicinal plants, inventory, Parepare City, South Sulawesi.